Colorimetric Metal‐Free Detection of Carbon Monoxide: Reversible CO Uptake by a BNB Frustrated Lewis Pair. Issue 30 (22nd June 2021) - Zheng, Xiongfei; Zulkifly, Ili; Heilmann, Andreas; McManus, Caitilín; Aldridge, Simon
Abstract: We report two BNB‐type frustrated Lewis pairs which feature an acceptor‐donor‐acceptor functionalized cavity, and which differ in the nature of the B‐bound fluoroaryl group (C6 F5 vs. C6 H3 (CF3 )2 ‐3, 5, Ar f ). These receptor systems are capable of capturing gaseous CO, and in the case of the ‐BAr f 2 system this can be shown to occur in reversible fashion at/above room temperature. For both systems, the binding event is accompanied by migration of one of the aryl substituents to the electrophilic carbon of the CO guest. Experiments utilizing an additional equivalent of P t Bu3 allow the initially formed (non‐migrated) CO adduct to be identified and trapped (via demethylation), while also establishing the reversibility of the B‐to‐C migration process. When partnered with the slightly less Lewis acidic ‐BAr f 2 substituent, this reversibility allows for release of the captured carbon monoxide in the temperature range 40–70 °C, and the possibility for CO sensing, making use of the associated colourless to orange/red colour change. Abstract : Acridan‐derived receptors featuring an acceptor‐donor‐acceptor functionalized cavity offer a metal‐free approach for binding carbon monoxide. Reversibility can be tuned through borane Lewis acidity and the binding event signalled colorimetrically.